(untitled) (Research, Society and Development, 2024)
Introduction: Duchenne Muscular Dystrophy (DMD) is an X-linked recessive genetic disease caused by mutations in the DMD gene, which encodes the protein dystrophin. As a result, repeated muscle injuries occur, leading to challenges in mobility, as well as cardiorespiratory complications. Objective: To investigate the prevalence of DMD in the global population. Methodology: The study search was conducted using the descriptors: "Duchenne Muscular Dystrophy" AND "Prevalence", in MEDLINE-PubMed, Embase, Lilacs, SCIELO, and Web of Science. Eligibility, screening, and data extraction were conducted by three reviewers. The software R was used for the meta-analysis. Results: A total of 2,155 studies were identified. Of these, 2,146 articles were excluded after reading the titles, abstracts, and full texts. Nine studies (n = 21,447,765 patients) reported data on the prevalence of DMD in patients. Overall, the prevalence of dystrophy was 1.04 per 10,000 individuals (95% CI 0.00 to 2.41, I² = 99%, p < 0.01). All DMD patients were male. A statistically significant difference was observed in the subgroup analysis by continent, with a higher prevalence in North America 1.28% (95% CI 0.71–1.85), and the most common genetic mutation type in the DMD gene was deletion 78% (95% CI 42–85). Conclusion: DMD is a prevalent dystrophic disease, mainly affecting male individuals and those from the North American continent, and is primarily caused by deletion-type genetic mutations.